Broad spectral sliced multiwavelength source with a mode locked fiber laser - Shahabuddin, Nurul Shahrizan; Mohamad, Hafizah; Mahdi, Mohd Adzir; Yusoff, Zulfadzli; Ahmad, Harith; Harun, Sulaiman Wadi (IOP Publishing, 2012)
A simple multi-wavelength source is demonstrated based on spectral slicing of supercontinuum (SC) light using a Sagnac loop mirror. A mode locked fiber laser with pulse width of 800 fs is employed to generate the SC in photonic crystal fiber (PCF). The SC light extending from 1200 nm up to the wavelength region above 1750 nm is obtained at the amplified pulse pump power of 30 dBm. By slicing the SC with a loop mirror, a multiwavelength comb spectrum is obtained with different channel spacing for different operating wavelength region. Spacings of 1.5, 2.3, and 2.9 nm are shown at wavelength regions of 1220, 1450, and 1730 nm, respectively. It is also observed that the signal to noise ratio (SNR) increases from 15 to 20 dB as the operating wavelength increases from 1220 to 1730 nm region.